Domain Engineering of Software Product Lines with Service-Oriented Architecture - Queiroz, Paulo G. G.; Braga, Rosana T. V. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2010)
Software product lines (SPL) have been established as one of the best ways to promote reuse of both requirements and software architecture, even with a high cost when compared to the development of single systems. Service-oriented architecture (SOA) can further facilitate the development of SPL, since several features of the SPL can be implemented by services available on a network. This paper presents SoProL-WS, which is a development approach for SPL using SOA. The focus of this article is in the domain engineering phase, where the SPL architecture is developed based on services. From this architecture, one can derive products in the subsequent application engineering phase. The goal of SoProL-WS is to reduce SPL development costs and time, facilitating its maintenance, evolution and derivation of its members. Additionally, this paper presents a case study where SoProl-WS is applied to develop a product line for Web auctions.